The effectiveness of the use of picture in series in narrative writing - Tan, Wilson (2019)
The aim of this study was to explore the impact of picture series where a class of Form 4 students engaged into narrative writing process and to suggest picture series as a way to improve the students’ performance in narrative writing. Besides, English as Second Language (ESL) teachers’ perspectives on the use of picture series in narrative writing are explored. This study had employed pre-and post-test along with questionnaires and it was conducted in SMK Methodist (ACS), Kampar, Perak for a duration of 6 weeks. The major findings of this research paper showed that majority of the Form 4 students studied improved after receiving the intervention given. ESL teachers were giving positive feedbacks on the use of picture series in narrative writing in the class. Future researchers should conduct the study in the whole Perak district can be generalizable and proof that it is able to help students in narrative writing.